2015
DOI: 10.1038/ncomms9504
|View full text |Cite
|
Sign up to set email alerts
|

Edge-mediated skyrmion chain and its collective dynamics in a confined geometry

Abstract: The emergence of a topologically nontrivial vortex-like magnetic structure, the magnetic skyrmion, has launched new concepts for memory devices. Extensive studies have theoretically demonstrated the ability to encode information bits by using a chain of skyrmions in one-dimensional nanostripes. Here, we report experimental observation of the skyrmion chain in FeGe nanostripes by using high-resolution Lorentz transmission electron microscopy. Under an applied magnetic field, we observe that the helical ground s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
217
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 230 publications
(239 citation statements)
references
References 26 publications
19
217
3
Order By: Relevance
“…Very recently, Du et al reported on real-space observation of a cascade of transitions in the magnetic structure of a FeGe wire [34]. Although this system stabilizes Bloch skyrmions, this work gives experimental corroboration of many of our findings, such as the existence of elongated skyrmions, the creation of skyrmions from edge states, and the enhanced stability of skyrmions in the confining geometry.…”
Section: Fig 1 (Color Online)supporting
confidence: 83%
“…Very recently, Du et al reported on real-space observation of a cascade of transitions in the magnetic structure of a FeGe wire [34]. Although this system stabilizes Bloch skyrmions, this work gives experimental corroboration of many of our findings, such as the existence of elongated skyrmions, the creation of skyrmions from edge states, and the enhanced stability of skyrmions in the confining geometry.…”
Section: Fig 1 (Color Online)supporting
confidence: 83%
“…For TEM measurements in a cross-sectional geometry, the Fresnel fringes generated by the film/substrate and film/cap interfaces wash out any magnetic contrast, unless the electron scattering potential of the chiral magnet is matched to the surrounding material, as was accomplished in Pt/FeGe/Pt nanostructures 24 . This is not the case for MnSi/Si interfaces where there is appreciable electron density differences, and neutron scattering is better suited to investigate the buried magnetic structures in this case.…”
Section: Methodsmentioning
confidence: 99%
“…The latter likely plays the dominant role in creating stable skyrmions in free-standing chiral magnetic nano-crystals [21][22][23][24] . Studies of the thickness dependence of the magnetic structure in wedgeshaped specimens reveals the influence of confinement on the skyrmions' stability 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…At H ≈ 1.96 kOe, the elongated skyrmions shrink into circles and assemble along the edge (Fig. 1F), indicating the attractive interaction among them (8,17).…”
Section: Significancementioning
confidence: 99%
“…1 G-J) (4,17). Finally, this triskyrmion cluster with triangular arrangement is formed in a wide interval of magnetic fields (1.96 kOe < H < 3.70 kOe), although the position of each individual skyrmion in the cluster can adjust correspondingly with the varied H (23).…”
Section: Significancementioning
confidence: 99%